2021
DOI: 10.1108/ijchm-11-2020-1348
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting customer loyalty toward mobile e-commerce in the hospitality industry: does brand viscosity matter?

Abstract: Purpose To better understand how to retain hospitality customers in the fierce competition among mobile applications, this study aims to propose and empirically validates an integrative framework, which elaborates how conscious and subconscious factors, together with affective factors, may induce app loyalty and how brand viscosity moderates such effects. Design/methodology/approach The authors conducted an online survey to collect data and received a total of 268 valid responses. This study splits the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Recent studies on consumer inertia have concentrated on the information technologies fields and discussed why consumers are unwilling to use novel technologies and instead prefer to maintain the status quo (Choi, 2020; Wang et al , 2019; Wu et al , 2021). Inertia has also become a popular concept in research on consumer psychology (Shiu and Tzeng, 2018) and service marketing (Carter et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on consumer inertia have concentrated on the information technologies fields and discussed why consumers are unwilling to use novel technologies and instead prefer to maintain the status quo (Choi, 2020; Wang et al , 2019; Wu et al , 2021). Inertia has also become a popular concept in research on consumer psychology (Shiu and Tzeng, 2018) and service marketing (Carter et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consumer inertia can occur among consumers who consistently overlook better alternatives in favor of repurchasing the same brands or products, influencing the decisions of enterprises (MacKay and Remer, 2022) as well as consumers (Hortaçsu et al , 2017), thereby fostering retention (Cui et al , 2020). This phenomenon has been found to apply to products and services such as operating systems (Polites and Karahanna, 2012), smartphones (Gray et al , 2017), cloud services (Lucia-Palacios et al , 2016), mobile applications (Wu et al , 2021) and banking industry (Nel and Boshoff, 2021). However, apart from Han et al (2011) and Chark and King (2021), work on inertia in the hospitality setting remains thin (Chark and King, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, branding hospitality services takes a different strategy than branding physical commodities. Because hospitality service firms rely significantly on their workers to fulfill the marketing goals, there is a growing worry about how to manage their brand-related behavioral patterns (Andaji Garmaroudi et al, 2021 ; Buhalis and Park, 2021 ; Robinot et al, 2021 ; Wu et al, 2021 ). Resultantly, internal branding has already been brought to the branding literature, which is concerned with matching staff activities with brand promise (Kaushal and Srivastava, 2021 ; Solakis et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…(Jiang and Wen, 2020). However,Wu et al (2021) stated that SM could play an essential role in user engagement during COVID-19, reducing people's fear. Furthermore, a study byAhmad et al (2021) identified that engagement on SM platforms during COVID-19 helped Malaysian citizens overcome anxiety and distrust towards all services provided by the country.…”
mentioning
confidence: 99%